(untitled) (Medico Legal Update, 2020)
The golden nanoparticles were prepared by pulse laser ablation (PLA) by the liquid phase method. Lasers (Nd: Yag) (1064nm (80mJ) wavelength) are used in different pulses (200, 400, and 600), and deionized distilled liquid water (DDDW) is used The prepared nanomaterial was added by laser ablation and with three laser pulses to a peaceful blood sample, where the nanomaterial was added in different concentrations 2, 4, 5 ml to 1 ml of blood. A blood image was taken for each sample, where the total samples became 9 samples and compared with a sample of healthy blood. It was observed that the general observation of rates and in general of all components of blood tissues has decreased significantly and very dangerous and also frightening with increasing concentration of both nanomaterial’s and increased number of laser pulses per minute compared to normal rates and control sample readings